Polimorfisme Gen Ferroportin (FPN1) Q248H dan Karakteristik Sosial Ekonomi Ibu Hamil dengan Anemia di Surakarta - Istiqomah, Nor; Dewi, Vitria Sari; Farmawati, Arta; Sadewa, Ahmad Hamim; Soesilo, Yuliana Heri; Damayanti, Kusumadewi Eka; Indarto, Dono (Pena Medika Jurnal Kesehatan, 2013)
Background: Iron deficiency anemia in pregnancy remains an important health problem in Indonesia. Ferroportin (FPN1) is one of important gene in iron metabolism encodes ferroportin for iron absorption, release, and recycle inside the body. The polymorphism of FPN1 Q248H alters negative charge of the amino acid sequence positively, hence influenced its ubiquitination and degradation. Beside of that, the high prevalence of anemia not only caused by genetics, nutrition, physiology of each pregant women, but also demographic factor and sosio-economic burden of family. This research will study the polymorphism of ferroportin Q248H and demographic character in pregnant women in Surakarta.Methods: The study using descriptive analytic case-control approach. The data used were from questionaire and blood sampling whose counted for screening anemia in private laboratorium. Pregnant women who had intention and had 10-25 week in pregnant were selected to be research subject.  FPN1 Q248H polymorphism were determined using PCR-RFLP method. Analysis Chi-square dan Independent t-test used to conclude the relationship between each variable to anemic state of pregnant women in Surakarta. A p<0.05 was considered as significant. The study using decriptive analytic design method. Results: Prevalence of anemia in Surakarta is 25.7% with 80.7% have mild anemia. There was no varian in FPN1 Q248H. Majority of pregnant women in group of anaemia have demographic character like 20-25 old, multigravid, last education in High School, housewife, their income range from Rp 500.000,00 to Rp 1.000.000,00, and consume Fe tablet. The bivariat analysis show no statistical significancy of parity, maternal age, education, income, and comsumption of iron tablet to state of anaemia (p>0.05).Conclusions: The FPN1 Q248H polymorphism was not a risk factor for iron deficiency anemia in pregnant women, likewise socio-economic factors had no significant role to incidence of anemia in Surakarta. Keywords: Anemia in pregnancy, Ferroportin (FPN1) Q248H polymorphism, Socio-Economic